Measuring Productive Derivational Knowledge of the Most Frequent Words - Barouni Ebrahimi, Alireza (International Journal of English Studies, 2021)
Derivational knowledge is associated with writing and speaking skills. These skills are essential for EFL students who express themselves in oral presentations or written assignments. Therefore, diagnostic measurement of productive derivational knowledge is of vital importance, especially in regard to the most frequent 1,000 word families that cover 81% and 85% of written and spoken text. This study measured 46 Iranian university EFL students’ productive derivational knowledge of the words at the 1,000 word frequency level. The findings indicate that while participants had the productive form-meaning knowledge of the words at 1,000 level, they did not seem to have extensive derivational knowledge of the same words. This assists in diagnosing area of weakness and placing instructional emphasis on high frequency words.